Self-Defocusing of Light in Ethanol Around 1550 nm - Jun Yi; Lili Miao; Jie Li; Qian Yi; Jing Huang; Chujun Zhao (IEEE Photonics Journal)
We experimentally investigated the third-order nonlinear optical response of absolute ethanol around 1550 nm. The real and imaginary parts of third-order susceptibilities are distinguished by Z-scan method, which demonstrated that absolute ethanol exhibited saturable absorption and self-defocusing behaviors with nonlinear refractive index n2∼−10−14 m2/W. In addition, the experimental results via self-phase modulation method also verified the comparable nonlinear optical response of absolute ethanol. This work is expected to provide insights for the nonlinearities of organic solvents, and may broaden the potential of cost-effective nonlinear optoelectronic devices.